Diagnostic delay in psychogenic seizures and the association with anti-seizure medication trials. (August 2016) - Kerr, Wesley T.; Janio, Emily A.; Le, Justine M.; Hori, Jessica M.; Patel, Akash B.; Gallardo, Norma L.; Bauirjan, Janar; Chau, Andrea M.; D'Ambrosio, Shannon R.; Cho, Andrew Y.; Engel, Jerome; Cohen, Mark S.; et al.
Abstract: Purpose: The average delay from first seizure to diagnosis of psychogenic non-epileptic seizures (PNES) is over 7 years. The reason for this delay is not well understood. We hypothesized that a perceived decrease in seizure frequency after starting an anti-seizure medication (ASM) may contribute to longer delays, but the frequency of such a response has not been well established. Methods: Time from onset to diagnosis, medication history and associated seizure frequency was acquired from the medical records of 297 consecutive patients with PNES diagnosed using video-electroencephalographic monitoring. Exponential regression was used to model the effect of medication trials and response on diagnostic delay. Results: Mean diagnostic delay was 8.4 years (min 1 day, max 52 years). The robust average diagnostic delay was 2.8 years (95% CI: 2.2–3.5 years) based on an exponential model as 10 to the mean of log10 delay. Each ASM trial increased the robust average delay exponentially by at least one third of a year (Wald t = 3.6, p = 0.004). Response to ASM trials did not significantly change diagnostic delay (Wald t = −0.9, p = 0.38). Conclusion: Although a response to ASMs was observed commonly in these patients with PNES, the presence of a response was not associated with longer time until definitive diagnosis. Instead, the number of ASMs tried was associated with a longer delay until diagnosis, suggesting that ASM trials were continued despite lack of response. These data support the guideline that patients with seizures should be referred to epilepsy care centers after failure of two medication trials.